Parents' Perspectives on How to Improve the Childhood Vaccination Process. (March 2017) - Lieu, Tracy A.; Zikmund-Fisher, Brian J.; Chou, Cathy; Ray, G. Thomas; Wittenberg, Eve
Few national studies have asked parents how to improve the childhood vaccination process. We surveyed a nationally representative online panel of parents on how to improve this process, rationales for nonstandard approaches, and alternatives to the standard schedule. Twelve percent of the 1222 respondents reported using nonstandard approaches: 3.2% used a specific schedule, 6.0% had no specific schedule, and 2.5% declined all vaccinations. The most common rationales were that too many vaccines are given at once, and discomfort with vaccine ingredients. Regarding how to improve the process, parents using the standard schedule most often said nothing could be improved (51%), or better vaccine information (22%). Those using nonstandard approaches most often would have liked more choice (40%) or better vaccine information (26%). Parents' experiences with the vaccination process could be improved by offering information prior to visits, giving more information about side effects, and allowing more flexibility about vaccine scheduling.